Ultracold atom-molecule collisions with fermionic atoms - D’Incao, J. P.; Esry, B. D.; Greene, Chris H. (My University, 2008)
Elastic and inelastic properties of weakly bound s- and p-wave molecules of fermionic atoms that collide with a third atom are investigated. Analysis of calculated collisional properties of s-wave dimers of fermions in different spin states permit us to compare and highlight the physical mechanisms that determine the stability of s-wave and p-wave molecules. In contrast to s-wave molecules, the collisional properties of p-wave molecules are found to be largely insensitive to variations of the p-wave scattering length, and these collisions will usually result in short molecular lifetimes. We also discuss the importance of this result for both theories and experiments involving degenerate Fermi gases.